Investigation of bacteremia after toothbrushing in orthodontic patients - KADİR, TANJU (KOREAN ASSOC ORTHODONTISTS, 2009)
Objective: The aim of this study was to investigate the occurrence rate of bacteremia following toothbrushing with toothpastes composed of several antibacterial agents and compare the results with the conventional oral hygiene maintaining methods in orthodontic patients. Methods: This clinical study included 100 adult orthodontic patients who were divided into 4 groups. Each group comprised of 25 patients, wearing fixed orthodontic appliances. In the first group, bacteremia was assessed after toothbrushing without using any toothpaste. In the second group, a 0.2% chlorhexidine gluconate mouthrinse was used before brushing with no toothpaste. In the third group, subjects brushed with a commonly used toothpaste which did not include an additional antimicrobial agent. The fourth experimental group used toothpaste which included tea tree oil, clove oil, peppermint oil and bisabolol as antimicrobial elements. Pre- and post-brushing blood samples were obtained using a strict aseptic technique. All samples were microbiologically evaluated using blood culture bottles. Results: Toothbrushing in orthodontic patients yielded to an increase in the occurrence rate of bacteremia when using normal toothpaste or no toothpaste at all. Conclusions: The use of chlorhexidine mouthwash before toothbrushing, and brushing with antimicrobial toothpaste did not show a statistically significant difference in preventing the occurrence of bacteremia (p > 0.05). (Korean J Orthod 2009;39(3):177-184)
Keywords: Bacteremia; Toothbrushing; Chlorhexidine gluconate; Antibacterial agents; TEA TREE OIL; TRANSIENT BACTEREMIA; INFECTIVE ENDOCARDITIS; MELALEUCA-ALTERNIFOLIA; ODONTOGENIC BACTEREMIA; ANTIMICROBIAL ACTIVITY; DENTAL EXTRACTION; ORAL BACTERIA; IN-VITRO; CHLORHEXIDINE